REG4 promotes the proliferation and anti-apoptosis of cancer - Zheng, Hua-Chuan; Xue, Hang; Zhang, Cong-Yu (Frontiers in Cell and Developmental Biology, 2022)
Regenerating islet-derived 4 (REG4) protein was discovered by high-throughput sequencing of ulcerative colitis, Crohn’s disease, and pancreatitis cDNA libraries. Regenerating islet-derived 4 is involved in infection and inflammation by enhancing macrophage polarization to M2, via activation of epidermal growth factor receptor (EGFR)/Akt/cAMP-responsive element binding and the killing inflammatory Escherichia coli, which is closely linked to tumorigenesis. Its expression was transcriptionally activated by caudal type homeobox 2, GATA binding protein 6, GLI family zinc finger 1, SRY-box transcription factor 9, CD44 intracytoplasmic domain, activating transcription factor 2, and specificity protein 1, and translationally activated by microRNA-24. Regenerating islet-derived 4 can interact with transmembrane CD44, EGFR, G protein-coupled receptor 37, and the polysaccharide, mannan, on cancer cells. Its overexpression was observed in gastric, colorectal, pancreatic, gallbladder, ovarian and urothelial cancers, and is closely linked to their aggressive behaviors and a poor prognosis. Additionally, REG4 expression and recombinant REG4 aggravated such cellular phenotypes as tumorigenesis, proliferation, anti-apoptosis, chemoradioresistance, migration, invasion, peritoneal dissemination, tumor growth, and cancer stemness via EGFR/Akt/activator protein-1 and Akt/glycogen synthase kinase 3 β/β-catenin pathways. Sorted REG4-positive, deep crypt, secretory cells promote organoid formation of single Lgr5(+) colon stem cells by Notch inhibition and Wnt activation. Histologically, REG4 protein is specifically expressed in neuroendocrine tumors and signet ring cell carcinomas of the gastrointestinal tract, pancreas, ovary, and lung. It might support the histogenesis of gastric intestinal–metaplasia–globlet dysplasia–signet cell carcinoma. In this review, we summarized the structure, biological functions, and effects of REG4 on inflammation and cancer. We conclude that REG4 may be employed as a biomarker of tumorigenesis, subsequent progression and poor prognosis of cancer, and may be a useful target for gene therapy.